The Urgency of Social Media Restrictions for Sixteen-Year-Old Children from the Perspective of Legal Protection - Ar-Riski, Thiana Ayu; Handayani, Emi Puasa; Khayatudin (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The development of social media provides benefits for children in obtaining information, communicating, and developing themselves, but it also poses various risks, such as cyberbullying, digital exploitation, exposure to negative content, misuse of personal data, and disruption of psychological and social development. This study aims to analyze the urgency of restricting the use of social media for sixteen-year-olds from the perspective of legal protection and examine the form and implementation of regulations that can be applied. The research method used is normative legal research with a statutory and conceptual approach, using primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that restrictions on the use of social media for 16-year-olds have a strong urgency from juridical, psychological, and sociological aspects. Juridically, the protection is based on Article 28B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, the Child Protection Law, the Electronic Information and Transaction Law, the Personal Data Protection Law, and the Convention on the Rights of the Child, which prioritizes the principle of the best interests of children. The findings of the study show that legal protection can be realized through minimum age restrictions, age verification, supervision of use, protection of personal data, improvement of digital literacy, and strengthening the responsibility of digital platforms. The implementation of these policies requires synergy between the government, families, communities, and digital service providers to ensure child protection in the digital era.